Bergenin, a bioactive flavonoid: advancements in the prospects of anticancer mechanism, pharmacokinetics and nanoformulations - Pandey, Pratibha; Lakhanpal, Sorabh; Mahmood, Danish; Kang, Han Na; Kim, Byunggyu; Kang, Sojin; Choi, Jinwon; Moon, Seungjoon; Pandey, Shivam; Ballal, Suhas; Kumar, Sanjay; Khan, Fahad; et al. (Frontiers in Pharmacology, 2025)
The natural world is a vast reservoir of exceptionally varied and inventive chemical compositions. Natural products are used as initial compounds to create combinatorial libraries by targeted modifications and then by analyzing their structure-activity connections. This stage is regarded as a crucial milestone in drug discovery and development. Bergenin, a naturally occurring secondary metabolite, has been extracted from several plant components. It is a constituent found in herbal and Ayurvedic preparations. It demonstrates antiviral, antifungal, antitussive, antiplasmodial, anti-inflammatory, antihepatotoxic, antiarrhythmic, antitumor, antiulcerogenic, antidiabetic, and wound healing activities. Bergenin efficiently inhibited the proliferation of human cancer cells by stimulating the production of intracellular reactive oxygen species (ROS), causing DNA damage and leading to cell cycle arrest in the G1/G2 phases by blocking cell signaling pathways. More comprehensive reviews are needed on the anticancer properties of bergenin. Therefore, our review aimed to update the multifaceted benefits of bergenin to the future scientists and researchers, which can be leveraged to formulate safer and novel cancer therapies, while also establishing a robust framework for future investigations into bergenin in cancer treatment. More preclinical and clinical investigations are needed to validate the candidature of bergenin as a potent anticancer agent.